Synergistic lysosomal activatable polymeric nanoprobe encapsulating pH sensitive imidazole derivative for tumor diagnosis - Chen, Xiaohong (2020)
Developing optical tumor imaging probes with minimal background noise is very important for its early detection of small lesions and accurate diagnosis of cancer. To overcome the bottleneck of low signal to noise ratio and sensitivity, it needs further improvement in fluorescent probe design and understanding of tumor development process. Recent reports reveal that lysosome's acidity in cancer cells can be below 4.5 with high Na+ /H+ exchange activity, which makes it an ideal target intracellular organelle for cancer diagnosis based on the variation of pH. Herein, a boron 2-(2'-pyridyl) imidazole complex derivative (BOPIM-N) is developed, with the ability to show a pH-activatable "OFF-ON" fluorescent switch by inhibiting twisted intramolecular charge transfer upon protonation at pH 3.8-4.5, which is studied for its selective viable cancer cell imaging ability in both in vitro and in vivo experiments. Interestingly, BOPIM-N can specifically emit green fluorescence in lysosomes of cancer cells, indicating its promising cancer cell specific imaging ability. More importantly, nanoformulated BOPIM-N probes can be specifically light-ON in tumor bearing site of nude mice with resolution up to cellular level, indicating its potential application in tumor diagnosis and precision medicine.